The grave's a fine and private place [compact disc, unabridged] ; a Flavia de Luce novel - Bradley, Alan, 1938- (Bradley, Alan, 1938- Flavia de Luce mystery., 2018)
Twelve-year-old chemist prodigy Flavia de Luce is struggling to fill her empty days. If anything could take her mind off sorrow it's solving a murder, but the one she stumbles across this time may lead the young sleuth to an early grave.